Between the land and the sea : dunes as natural and cultural heritage - Freitas, Joana Gaspar de (2019)
Lecture given by the coordinator of the Project Dunes, Joana Gaspar de Freitas, during the CONCHA 2nd Workshop - Sea and Animals: History, Culture and Marine Conservation